Optimal dose of cefotaxime in neonates with early-onset sepsis: A developmental pharmacokinetic model-based evaluation - Shang, Zhen-Hai; Wu, Yue-E; Lv, Dong-Mei; Zhang, Wei; Liu, Wen-Qiang; van den Anker, John; Xu, Yan; Zhao, Wei (Frontiers in Pharmacology, 2022)
Objective: The perspective of real-world study is especially relevant to newborns, enabling dosage regimen optimization and regulatory approval of medications for use in newborns. The aim of the present study was to conduct a pharmacokinetic analysis of cefotaxime and evaluate the dosage used in newborns with early-onset sepsis (EOS) using real-world data in order to support the rational use in the clinical practice. Methods: This prospective, open-label study was performed in newborns with EOS. A developmental pharmacokinetic-pharmacodynamic model of cefotaxime in EOS patients was established based on an opportunistic sampling method. Then, clinical evaluation of cefotaxime was conducted in newborns with EOS using real-world data. Results: A one-compartment model with first-order elimination was developed, using 101 cefotaxime concentrations derived from 51 neonates (30.1-41.3 weeks postmenstrual age), combining current weight and postnatal age. The pharmacokinetic-pharmacodynamic target was defined as the free cefotaxime concentration above MIC during 70% of the dosing interval (70% fT＞MIC), and 100% of neonates receiving the dose of 50 mg/kg, BID attained the target evaluated using the model. Additionally, only two newborns had adverse reactions possibly related to cefotaxime treatment, including diarrhea and feeding intolerance. Conclusion: This prospective real-world study demonstrated that cefotaxime (50 mg/kg, BID) had a favorable efficacy and an accepted safety profile for neonates with EOS.